1977
DOI: 10.1111/j.1751-0813.1977.tb15812.x
|View full text |Cite
|
Sign up to set email alerts
|

The Epizootiology of Bovine Ephemeral Fever in Australia and Papua‐new Guinea

Abstract: The epizootiology of ephemeral fever in Australia from its first recognition until 1968 was reviewed. Since 1968, ephemeral fever often in a silent form has been shown to be enzootic in northern Australia, by the use of sentinel cattle. The major epizootics which occured in 1970-1971, 1972-1974 and 1974-1975 are described. These epizootics were characterised by an apparently rapid movement of disease in a general north-south direction in summer months. Ephemeral fever antibody was detected in 11% of 1009 domes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…However, there were 31 % of 391 cows which were 6 or more years old with clinical disease (Table 3). The cases in the older animals could be the result of individual cows not having encountered disease in earlier epidemics in the district (St George et al 1977;Kirkland 1982;Uren et al 1983), or perhaps due to intercurrent infection with other arboviruses as suggested by St George (1985), or a waning of immunity with age.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, there were 31 % of 391 cows which were 6 or more years old with clinical disease (Table 3). The cases in the older animals could be the result of individual cows not having encountered disease in earlier epidemics in the district (St George et al 1977;Kirkland 1982;Uren et al 1983), or perhaps due to intercurrent infection with other arboviruses as suggested by St George (1985), or a waning of immunity with age.…”
Section: Discussionmentioning
confidence: 96%
“…The maps which illustrate the epidemics of 1936-37 by (Seddon 1938;Murray 1970;St George et at. 1977), and to a lesser extent by Uren et at.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method used was the intracerebral inoculation of suckling mice as described by St George et al (1977).…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…Consequently the procedure of carrying out insect collections only where and when an epidemic occurred was revised to that of collecting continuously 0004-9417/84/050351 $02.00 in an area where there was a high probability that infection of cattle with bovine ephemeral fever would occur. Beatrice Hill in the Northern Territory was selected because sentinel herd serology (St George et al 1977) indicated that bovine ephemeral fever would be encountered if collections were made to cover two wet seasons. Laboratory facilities were available on site, and importantly, access by road was possible throughout the year.…”
Section: Introductionmentioning
confidence: 99%